2020
DOI: 10.3390/vaccines8030480
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Vaccination Uptake in Risk Populations: A Comprehensive Literature Review

Abstract: Vaccination uptake has decreased globally in recent years, with a subsequent rise of vaccine-preventable diseases. Travellers, immunocompromised patients (ICP), and healthcare workers (HCW) are groups at increased risk for (severe) infectious diseases due to their behaviour, health, or occupation, respectively. While targeted vaccination guidelines are available, vaccination uptake seems low. In this review, we give a comprehensive overview of determinants—based on the integrated change model—predicting vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 108 publications
(134 reference statements)
7
43
0
Order By: Relevance
“…Older people tend to be more compliant with vaccination guidelines, especially for influenza vaccination. In addition, older healthcare workers usually have a significantly higher uptake of vaccines, in general [11]. Our results show an association between age and high acceptance of COVID-19 vaccination.…”
Section: Plos Onementioning
confidence: 55%
“…Older people tend to be more compliant with vaccination guidelines, especially for influenza vaccination. In addition, older healthcare workers usually have a significantly higher uptake of vaccines, in general [11]. Our results show an association between age and high acceptance of COVID-19 vaccination.…”
Section: Plos Onementioning
confidence: 55%
“…The large data set from previous studies has shown that apart from rolling, an important role in various medical-related behaviours. Such as perceptions of disease severity, adherence to treatment [26], and vaccination decisions [27], perceived risk is also empirically proven to be closely related and strongly influence vaccination intention [23], [28]- [31].…”
Section: Introductionmentioning
confidence: 99%
“…Advice and recommendations from healthcare professionals is the most common reason for vaccinehesitant parents changing their minds 15 and is one of the strongest predictors of vaccination acceptance [29][30] . Conversely, people have cited a lack of GP recommendation as the cause for being vaccine-hesitant 21 .…”
Section: Discussing Vaccines and Addressing Vaccine Hesitancymentioning
confidence: 99%